Prognostic significance of the aberrant expression of neuroendocrine markers in melanomas - Yan Wu; Yumei Lai; Miao Zhang; Zhongwu Li (BMC, 2021)
Abstract Background Melanoma is a highly malignant tumor with diverse histopathological morphology and frequent aberrant expression of immunohistochemical markers. An occasionally reported phenomenon is the abnormal expression of neuroendocrine markers. Awareness of this situation is essential because such tumors need to be differentiated from neuroendocrine tumors because of their significant therapeutic and prognostic implications. Methods We retrospectively analyzed the expression of chromogranin A (CgA), synaptophysin (Syn) and CD56 as neuroendocrine markers in 308 cases with melanomas. Kaplan-Meier curves and Cox regression analyses were used for overall survival (OS) and progression-free survival (PFS) evaluation and comparison between neuroendocrine markers expression status in all melanoma cases or stage I-II cases. Results The expression of neuroendocrine markers in melanomas is not uncommon. CgA was positive in 6/304 (2.0%) cases, Syn in 26/304 (8.6%), and CD56 in 56/189 (29.6%). None of the cases co-expressed all the three markers. Focal or weak expression of at least one neuroendocrine marker was identified in 70/188 (37.2%) cases. The expression of CgA was correlated with age (p = 0.019), while the positive expression of Syn and CD56 showed borderline significance (p = 0.078 and 0.083, respectively), but not for any neuroendocrine marker expression. The expression of any neuroendocrine marker showed borderline significance with staging (p = 0.066). The expression of CgA, Syn, CD56, or any neuroendocrine marker did not correlate with clinicopathological features including sex, specimen type, origin, location, and histology subtype. Survival analyses revealed that the expression of neuroendocrine markers was not associated with OS or PFS. Conclusions Our study confirms that neuroendocrine marker expression is a common phenomenon in melanomas, but it has no prognostic significance. Nevertheless, awareness can avoid misdiagnosis in cases of melanomas with unusual morphology and immunophenotypes.